Purifikasi dan Karakterisasi Î±-amilase Termostabil dari Bacillus stearothermophilus TII-12 - Lestari, Puji; Richana, Nur; Darwis, Abdul Aziz; Syamsu, Khaswar; Murdiyatmo, Untung (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
Purification and Characterization of ThermostableÎ±-amylase from Bacillus stearothermophilus TII-12. PujiLestari, Nur Richana, Abdul A. Darwis, Khaswar Syamsu,and Untung Murdiyatmo. Thermostable Î±-amylase is apotential enzyme employed in the starch processing andwidely used in food industries, but this enzyme is stillimported. The local enzyme production would be moreeconomist and useful for its broad applications. Here wereport Î±-amylase from indigenous bacteria TII-12 which waspurified and characterized, as well as analyzed its hydrolysisproduct on cassava starch. The enzyme of Bacillusstearothermophilus TII-12 partially purified by ultrafiltration,acetone precipitation and gel filtration (Sephadex G-100)showed the reduced total activity, total protein and yield, butincreased the specific activity. The enzyme had a Km of 1,06mg/ml and Vmax of 1,21 mol/min, with optimal activity at pH 7and 90oC. An apparent molecular mass was of 192.932,8Dalton, as estimated by Native-Polyacrylamide Agarose Gelelectrophoresis. Its activity was inhibited by the divalentcation chelator such as EDTA and CuSO4 but activated bycalcium ion. Hydrolysis products of this enzyme on cassavastarch were glucose, dextrin, maltose and oligosaccharides.After 24 hours of hydrolysis, the concentration of glucoseand maltose reached 51.970 and 10.090 ppm, respectively.The thermostable Î±-amylase of TII-12 is an endo-Î±-amylaseand prospective to be applied on starch liquefaction withhigh temperature process.